Spin polarized 3He: from basic research to medical applications - Karpuk, Sergei; Allmendinger, Fabian; Burghoff, M.; Gemmel, C.; Güldner, M.; Heil, W.; Kilian, W.; Knappe-Grüneberg, S.; Mrozik, Ch.; Müller, W.; Otten, E. W.; Repetto, M.; et al. (Physics of particles and nuclei, 2013)
Polarization of 3He gas by means of optical pumping is well known since the early 1960s with first applications in fundamental physics. Some thirty years later it was discovered, that one can use hyperpolarized 3He as contrast agent for magnetic resonance imaging of the lung. The wide interest in this new method made it necessary to find ways of polarizing 3He in large quantities with high polarization degrees. A high performance polarizing facility has been developed at the University of Mainz, designed for centralized production of hyperpolarized 3He gas. We present the Mainz concept as well as some examples of numerous applications of spin polarized 3He in fundamental research and medical applications.